Assessment of anterior and posterior corneal indices using two Scheimpflug analyzers - Fahd,Daoud Charbel (2014)
Purpose: To assess the agreement between the elevation and curvature measurements of the anterior and posterior corneal surfaces obtained using the Galilei Dual Scheimpflug Analyzer and those obtained using the Pentacam single Scheimpflug system. Methods: This prospective, noninterventional, diagnostic study was conducted at the Department of Ophthalmology at the American University of Beirut (Medical Center) and included 60 eyes of 60 consecutive patients. Measurements were obtained using 2 different Scheimpflug analyzers (Galilei and Pentacam). The best-fit sphere was set at 8 mm in both machines. Pachymetry (CCT), anterior elevation (AE) and posterior elevation (PE), and curvature were assessed. Pearson's correlation coefficients, comparison of means, and Bland-Altman plots were used to evaluate agreement between the 2 systems. Results: The average CCT (at the corneal apex) was 533 ± 35 µm and 532 ± 37 µm (p=0.980), the average central AE was 1.25 ± 3.95 µm and 2.29 ± 5.28 µm (p=0.964), and the average central PE was 4.19 ± 8.18 µm and 5.42 ± 14.05 (p=0.956) µm with the Galilei and Pentacam, respectively. Conclusion: The Scheimpflug analyzers correlated well in the assessment of pachymetry, elevation, and curvature.